2020
DOI: 10.1177/1055665620933472
|View full text |Cite
|
Sign up to set email alerts
|

Contracted Extravelar Segments of the Levator Veli Palatini Muscle: A Magnetic Resonance Imaging Morphometric Study

Abstract: Objectives: To provide detailed descriptions of contraction-induced morphometric changes in the extravelar segments of the levator veli palatini (LVP) muscle using 3-dimensional (3-D) magnetic resonance imaging (MRI). Design: Three-dimensional MRI data were acquired at rest and during “silent /i/” from 4 singers. During silent /i/, participants voluntarily sustained velar elevation while breathing orally for the entire scan time. Focusing on the extravelar segments, LVP length, angle of the muscle origin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…LVP muscle morphology has been reported in the literature. 29,57,60 Kotlarek et al 57 reported significant differences in the LVP morphology and symmetry at the velum insertion points among children with repaired cleft palate and a greater degree of asymmetry was found in children with cleft-related velopharyngeal insufficiency. In contrast, Tahmasebifard et al 61 found no significant difference between right and left LVP muscle symmetry among participants without cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…LVP muscle morphology has been reported in the literature. 29,57,60 Kotlarek et al 57 reported significant differences in the LVP morphology and symmetry at the velum insertion points among children with repaired cleft palate and a greater degree of asymmetry was found in children with cleft-related velopharyngeal insufficiency. In contrast, Tahmasebifard et al 61 found no significant difference between right and left LVP muscle symmetry among participants without cleft palate.…”
Section: Discussionmentioning
confidence: 99%